PELAKSANAAN PEMBANGUNAN DESA DITINJAU DARI UNDANG – UNDANG NO 6 TAHUN 2014 TENTANG DESA (STUDI KASUS DESA LABUHAN JURUNG, KABUPATEN PADANG LAWAS UTARA) - Tohong Mektisen harahap (Eksekusi : Journal Of Law, 2020)
AbstractIn the implementation of village development, the village government does not carry out development in accordance with the plan or MUSDES then almost all development implementation is projected such as road construction leading to community plantations and construction of village halls or village offices which should be according to article 81 of Law No. 6 of 2014 on villages. should cooperate and make use of local wisdom and the village's existing natural resources. The factors inhibiting the function of the village head in village development are the geographical location, inadequate facilities and equipment.